ANALISIS HALAL, CITA RASA, DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PADA ARABIANS KEBAB DI UMS SURAKARTA) - Insan Setiawan; Eny Kustiyah; Siti Maryam (ITB AAS INDONESIA Surakarta, 2022)
This study aims to analyze and discuss the effect of halal, taste, product variation on product purchasing decisions at Arabians Kebab UMS Surakarta. The research used is descriptive quantitative research. The population in this study were the customers of Arabians Kebab UMS Surakarta. The sample consisted of 100 respondents using accidental sampling technique. The data analysis technique used Multiple Linear Regression Analysis. The F test results show that halal, taste, and product variations simultaneously have a significant effect on purchasing decisions. While the t test results show that partially halal has a positive and significant effect on purchasing decisions, taste partially has a positive and significant effect on purchasing decisions and also product variations partially have a positive and significant effect on purchasing decisions at Arabians Kebab UMS Surakarta. Keywords: halal, taste, product variation, purchase decision.